Q Group Panel Discussion: Looking to the Future. Issue 4 (1st July 2016) - Leibowitz, Martin; Lo, Andrew W.; Merton, Robert C.; Ross, Stephen A.; Siegel, Jeremy
Abstract : At the Q Group (the Institute for Quantitative Research in Finance) Spring Seminar, held 17–20 April 2016, Martin Leibowitz moderated a discussion of the important issues in finance by panelists Andrew W. Lo, Robert C. Merton, Stephen A. Ross, and Jeremy Siegel. Abstract : Editor's note: We wish to thank the Q Group for allowing us to publish an edited version of this panel discussion, held 19 April 2016, and thus making the panelists' comments available to a wide audience.